Effectiveness of topical combination of finasterid and minoxidil in the management of male androgenetic alopesia (systematic review and meta-analysis: Hair density study) - Riyanto, Puguh; Karami, Muhammad Zuldan; Malik, Diah Adriani (Institute of Computer Science (IOCS), 2025)
Androgenetic alopecia (AAG) is the most common hair loss problem in men, characterized by miniaturization of hair follicles due to systemic androgens and genetic factors. AAG treatment aims to prevent follicle miniaturization Treatment modalities for AAG include hair transplantation, platelet-rich plasma (PRP), microneedling, and stem cells. Each treatment modality has its benefits and risks. The combination of topical finasteride and topical minoxidil has been shown to improve outcomes in several studies. This study aimed to evaluate the efficacy of topical finasteride compared to topical minoxidil in improving hair density among male AAG patients. A systematic literature search method was conducted using MEDLINE, Embase, AMED, Cochrane Library, Clinicaltrials.gov, Web of Knowledge, Web of Science, and WHO ICTRP with the search terms